Bronchoalveolar Lavage Fluid-Derived Exosomes: A Novel Role Contributing to Lung Cancer Growth - Yang, Yibao; Ji, Ping; Wang, Xuan; Zhou, Hao; Wu, Junlu; Quan, Wenqing; Shang, Anquan; Sun, Junjun; Gu, Chenzheng; Firrman, Jenni; Xiao, Weidong; Sun, Zujun; et al. (Frontiers in Oncology, 2019)
Exosomes are nanovesicles produced by a number of different cell types and regarded as important mediators of cell-to-cell communication. Although bronchoalveolar lavage fluid (BALF) have been shown to be involved in the development of tumor, their role in lung cancer remains unclear. Here we systemically studied BALF-derived exosomes in lung cancer. When C57BL/6 mice were injected with Lewis lung carcinoma cells (LLC cells) then exposed to Nontypeable Haemophilus influenza (NTHi) lysate, lung tumor growth in these mice was significant enhanced as compared to the control cohort with only air exposure. Characterization of exosomes derived from mouse BALF demonstrated elevated levels of tumor necrosis factor alpha (TNF-α) and Interleukin-6 (IL-6) in mice exposed to NTHI lysate. Furthermore, abnormal BALF-derived exosomes facilitated the development of LC in vitro and in vivo. The internalization of the BALF-derived exosomes contributed to the development of tumor in LC. Taken together, our data demonstrated that exosomes in BALF are a key factor involving in the growth and progression of lung cancer.